Anti-infection microneedle mask and preparation method thereof

The anti-infection microneedle mask, which combines chitosan-silver composite particles with modified polylactic acid-glycolic acid nanofiber capsules, solves the problems of insufficient mechanical strength, poor antibacterial properties, and high infection risk of traditional microneedle masks, and achieves highly efficient skin penetration and antibacterial effects.

CN121015489APending Publication Date: 2025-11-28ARTIFACT R&D (SUZHOU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511193665.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Traditional microneedle masks suffer from insufficient mechanical strength, fragility, intense pain, poor antibacterial properties, and high risk of infection when penetrating the skin.

Method used

An anti-infection microneedle mask was prepared by combining chitosan-silver composite particles with modified polylactic acid-glycolic acid nanofiber capsules. A three-dimensional nanofiber capsule structure was constructed by positive and negative electrospinning technology. Combined with the biocompatibility of chitosan encapsulation layer and the sustained-release properties of PLGA, a multiple antibacterial mechanism was formed.

Benefits of technology

It achieves ideal mechanical strength and penetration capability of microneedles, extremely low infection rate and pain score, excellent antibacterial effect, avoids burst release stimulation of active ingredients, and provides more efficient distribution of active ingredients and antibacterial performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of external preparations, in particular to an anti-infection microneedle mask and a preparation method thereof. According to the anti-infection micro-needle mask, the three-dimensional nanofiber balloon is adopted as a micro-needle carrier, a micro-needle array with excellent mechanical properties is constructed through a positive and negative opposite spraying electrostatic spinning technology, and meanwhile, the anti-infection micro-needle mask is prepared by combining the antibacterial function of the chitosan-silver composite particles and the biocompatibility of the chitin-bamboo fiber base cloth; and efficient transdermal drug delivery and infection protection are realized. The problems that a traditional micro-needle mask is insufficient in mechanical strength, low in antibacterial efficiency, large in skin irritation and prone to causing infection are solved through topological structure regulation and control of the nanofiber balloon innovatively, and the micro-needle mask has the advantages that puncture force is stable (0.9-1.0 N / needle), the antibacterial rate is larger than 99.7%, the skin irritation level is 0 and the like; the device is suitable for the field of medical art post-care and functional ingredient transdermal delivery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of external preparation, in particular to an anti-infection microneedle mask and a preparation method thereof. BACKGROUND

[0002] As a new type of beauty and skin care product, the microneedle mask can penetrate the stratum corneum of the skin through a microneedle array, promote the absorption of active ingredients of skin care products, and has good beauty effect. The traditional microneedle mask mainly uses a polymer matrix (such as hyaluronic acid, PLGA, etc.) combined with active ingredients to achieve transdermal delivery through physical puncture. For example, patent document CN119280105A discloses a soluble microneedle patch, microneedle mask, microneedle smoking cessation patch and a preparation method thereof. The microneedle mask includes a microneedle layer and a backing layer, which can solve the problems of insufficient mechanical strength of the soluble microneedle, inability to penetrate the skin for drug delivery, easy breakage during drug delivery, strong pain and poor comfort.

[0003] However, in order to balance the puncture performance and safety, a single polymer (such as PLGA) is often used for conventional microneedle materials, but there is a dilemma of insufficient strength or excessive hardness. Moreover, the existing antibacterial microneedles mostly use physical mixing of silver nanoparticles or antibiotics, which can easily form a small wound during the penetration of the skin, causing infection and affecting the safety and effect of use. SUMMARY

[0004] Therefore, the purpose of the present application is to provide an anti-infection microneedle mask and a preparation method thereof to solve the problems of high skin irritation and easy infection of the traditional microneedle mask.

[0005] To achieve the above purpose, the present application provides a preparation method of an anti-infection microneedle mask, and the specific steps are as follows: S1: adding deionized water to chitosan, adding glacial acetic acid to adjust the pH to 3-4, dissolving by magnetic stirring, then adding silver nitrate solution and stirring uniformly, adding sodium borohydride solution, stirring vigorously for 10-15 min, adding ammonia water to adjust the pH to 9-10, centrifuging after the precipitate appears, washing with deionized water for 2-3 times, washing with acetone for 1-2 times, and drying in a vacuum drying box for 10-12 h to obtain chitosan-silver composite particles; S2: dissolving polylactic acid-glycolic acid in a mixed solution of dichloromethane and N,N-dimethylformamide to obtain a polylactic acid-glycolic acid solution, then transferring the solution to a syringe, and fixing the syringe on an electrospinning machine, and performing spinning in a positive-negative spraying mode, and obtaining polylactic acid-glycolic acid nanofiber capsules after the spinning is completed; S3: The chitosan-silver composite particles were dispersed in a mixed solution of anhydrous ethanol and deionized water, and ultrasonic treatment was performed for 20 min to obtain a chitosan-silver composite particle dispersion, which was then transferred to a syringe, and the syringe was fixed on an ultrasonic spraying machine. The chitosan-silver composite particle dispersion was uniformly sprayed onto the surface of the nanofiber balloon, and then dried to obtain a modified polylactic acid-glycolic acid nanofiber balloon; S4: The polylactic acid-glycolic acid was dissolved in a mixed solvent of dichloromethane and N,N-dimethylformamide, and magnetic stirring was performed at 30℃ for 2h to obtain a uniform solution. Then, the modified polylactic acid-glycolic acid nanofiber balloon was added, and magnetic stirring was continued at 30℃ for 1h to obtain a microneedle matrix material, which was then added to the surface of the microneedle mold, centrifuged, and dried to obtain a microneedle array. S5: The chitin fibers and bamboo fibers were mixed, carded and laid to obtain a fiber web, which was then treated by a hydroentangled consolidation process to obtain a base cloth. Then, the base cloth was immersed in an ethanol aqueous solution containing 0.2% tea tree oil, and immersed at 40℃ for 60min. Finally, the ethanol and water were removed by hot air drying at 60℃ for 30min to obtain a mask base material. S6: The obtained microneedle array and mask base material were laminated under a sterile operating environment, and then irradiated for 30s under a UV light curing lamp to obtain an anti-infection microneedle mask.

[0006] The amount ratio of chitosan, deionized water, silver nitrate solution and sodium borohydride solution in step S1 was 4-5g: 50-100mL: 1-2g: 0.1-0.2g. The concentration of the silver nitrate solution in step S1 was 10mmol / L.

[0007] The concentration of the sodium borohydride solution in step S1 was 100mmol / L.

[0008] The weight ratio of polylactic acid-glycolic acid, dichloromethane and N,N-dimethylformamide in step S2 was 1.2-1.5g: 14-18g: 6-9g.

[0009] In step S2, the positive high voltage of electrospinning was +5kV, the spinning distance was 5cm, the 23G needle was used, and the flow rate was 1mL / h. The negative high voltage was -4.85kV, the spinning distance was 5cm, the 23G needle was used, and the flow rate was 1mL / h.

[0010] The amount ratio of chitosan-silver composite particles, anhydrous ethanol and deionized water in step S3 was 4-5g: 70-80mL: 20-30mL.

[0011] The ultrasonic current of the ultrasonic spraying machine in step S3 is 3.6 A, the propelling flow rate is 1 mL / min, the reciprocating spraying frequency is 12 times, the spraying speed is 95 mm / min, the rotating speed is 60 mm / min, the height of the spraying head is 35 mm, and the carrier gas pressure is 0.038 MPa.

[0012] The amount ratio of the polylactic acid-glycolic acid, dichloromethane, N,N-dimethylformamide and modified polylactic acid-glycolic acid nanofiber balloon in step S4 is 5-6 g:40 mL:10 mL:0.15-0.25 g.

[0013] The centrifugation in step S4 is centrifuged at a speed of 3000-4000 r / min for 10-20 min, and then centrifuged at a speed of 3000-4000 r / min for 5-10 min.

[0014] The molecular weight of the polylactic acid-glycolic acid in step S4 is 50000-70000 Da, and the molar ratio of lactic acid to glycolic acid is 75:25.

[0015] The amount ratio of the chitin fiber and bamboo fiber in step S5 is 60-70 g:30-40 g.

[0016] The amount ratio of the base cloth and 0.2% tea tree essential oil-containing ethanol aqueous solution in step S5 is 10 g:200 mL.

[0017] The deacetylation degree of the chitin fiber in step S5 is greater than or equal to 90%.

[0018] The fineness of the chitin fiber in step S5 is 1.2 denier.

[0019] The water jet pressure in step S5 is 110-1200 bar.

[0020] Further, the application also provides an anti-infection microneedle mask.

[0021] The application has the following beneficial effects: The anti-infection microneedle mask prepared by the application has a three-dimensional nanofiber balloon structure constructed by positive and negative spraying electrospinning technology, so that the microneedle has ideal mechanical strength and penetration ability, and a multiple antibacterial mechanism is formed due to the uniform distribution of chitosan-silver composite particles on the surface of the nanofiber balloon, so that the microneedle has excellent antibacterial effect; and the direct contact of silver nanoparticles with the skin is effectively blocked by the biocompatible wrapping layer of chitosan, and the burst release stimulation of active ingredients is avoided by the sustained release characteristics of the PLGA material, so that the infection rate is extremely low and the pain score is low.

[0022] The application introduces a modified polylactic acid-glycolic acid nanofiber balloon structure, a unique stress distribution network of the three-dimensional nanofiber balloon, the structure forms an elastic support frame through multidirectional connection of fiber nodes, which not only maintains the rigidity of the microneedle but also endows it with moderate deformation ability, meanwhile, surface functionalization treatment of the modified balloon creates a more efficient active site distribution mode, compared with physical mixing, the ordered assembly structure can more effectively improve the penetration ability, antibacterial performance and anti-infection ability of the microneedle mask.

[0023] The application provides a larger specific surface area and more uniform active ingredient distribution through the nanofiber balloon structure design, so that the chitosan-silver composite particles can be more fully contacted with microorganisms, and the problem that the antibacterial and anti-infection abilities are poor due to that part of the antibacterial sites are shielded because of uneven packing density in the traditional planar fiber structure is avoided. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the application clearer, the application is further described in detail below with specific examples.

[0025] The properties or sources of the raw materials used in the examples and comparative examples of the application are as follows: polylactic acid-glycolic acid: molecular weight is 50000-70000 Da, molar ratio of lactic acid to glycolic acid is 75:25; chitin fiber: deacetylation degree is greater than or equal to 90%; bamboo charcoal fiber: fineness is 1.2 denier.

[0026] Example 1: an anti-infection microneedle mask, the specific preparation steps are as follows: (1) 4 g of chitosan is added to 50 mL of deionized water, ice acetic acid is added to adjust the pH to 3, and magnetic stirring is used for dissolution, then 1 g of silver nitrate solution (10 mmol / L) is added and stirred uniformly, 0.1 g of sodium borohydride solution (100 mmol / L) is added dropwise, and after vigorous stirring for 10 min, ammonia water is added to adjust the pH to 9, and after the precipitate appears, centrifugal separation is performed, and the precipitate is washed with deionized water for 2-3 times and acetone for 1-2 times, and then dried in a vacuum drying box for 10 h to obtain chitosan-silver composite particles; (2) 1.2 g of polylactic acid-glycolic acid is dissolved in a mixed solution of 14 g of dichloromethane and 6 g of N,N-dimethylformamide to obtain a polylactic acid-glycolic acid solution, which is then transferred to a syringe, and the syringe is fixed on an electrospinning machine, and electrospinning is performed in a positive and negative spraying mode, and after the electrospinning is completed, polylactic acid-glycolic acid nanofiber balloons are obtained, wherein the positive high voltage is +5 kV, the spinning distance is 5 cm, the 23G needle is used, and the flow rate is 1 mL / h; the negative high voltage is -4.85 kV, the spinning distance is 5 cm, the 23G needle is used, and the flow rate is 1 mL / h; (3) 4 g of the chitosan-silver composite particles were dispersed in a mixed solution of 70 mL of anhydrous ethanol and 30 mL of deionized water, and ultrasonic treatment was performed for 20 min to obtain a chitosan-silver composite particle dispersion liquid, which was then transferred to a syringe, and the syringe was fixed on an ultrasonic spraying machine. The chitosan-silver composite particle dispersion liquid was uniformly sprayed onto the surface of the polylactic acid-glycolic acid nanofiber balloon, and dried to obtain a modified polylactic acid-glycolic acid nanofiber balloon. The ultrasonic current of the ultrasonic spraying machine was 3.6 A, the push flow was 1 mL / min, the reciprocating spraying times were 12 times, the spraying speed was 95 mm / min, the rotating speed was 60 mm / min, the nozzle height was 35 mm, and the carrier gas pressure was 0.038 MPa; (4) 5 g of polylactic acid-glycolic acid was dissolved in a mixed solvent of 40 mL of dichloromethane and 10 mL of N,N-dimethylformamide, and magnetic stirring was performed at 30°C for 2 h to obtain a uniform solution. Then, 0.15 g of the modified polylactic acid-glycolic acid nanofiber balloon was added, and magnetic stirring was continued at 30°C for 1 h to obtain a microneedle matrix material. Then, the microneedle matrix material was added to the surface of a microneedle mold, centrifuged at a speed of 3000 r / min for 10 min, and then centrifuged at a speed of 3000 r / min for 5 min for drying to obtain a microneedle array; (5) 60 g of chitin fibers and 40 g of bamboo fibers were thoroughly mixed, carded, and laid to obtain a fiber web, which was then treated by a hydroentanglement process at a hydroentanglement pressure of 110 bar to obtain a base cloth. Then, 10 g of the base cloth was immersed in 200 mL of an ethanol aqueous solution containing 0.2% tea tree essential oil, and immersed at 40°C for 60 min. Finally, the ethanol and water were removed by hot air drying at 60°C for 30 min to obtain a mask base material. (6) The obtained microneedle array and mask base material were laminated under a sterile operating environment, and then irradiated under a UV curing lamp for 30 s for curing to obtain an anti-infection microneedle mask.

[0027] Example 2: An anti-infection microneedle mask, the specific preparation steps are as follows: (1) 4.5 g of chitosan was added to 80 mL of deionized water, and the pH was adjusted to 3.4 by adding glacial acetic acid. The solution was dissolved by magnetic stirring, and then 1.5 g of silver nitrate solution (10 mmol / L) was added and stirred uniformly. Then, 0.15 g of sodium borohydride solution (100 mmol / L) was added dropwise, and the mixture was stirred vigorously for 13 min. Then, the pH was adjusted to 9.6 by adding ammonia water, and the precipitate was separated by centrifugation. The precipitate was washed with deionized water for 2-3 times and with acetone for 1-2 times, and then dried in a vacuum drying oven for 11 h to obtain chitosan-silver composite particles. (2) 1.4 g of polylactic acid-glycolic acid was dissolved in a mixed solution of 16 g of dichloromethane and 8 g of N,N-dimethylformamide, stirred uniformly to obtain a polylactic acid-glycolic acid solution, then transferred to a syringe, and the syringe was fixed on the electrospinning machine. The spinning was carried out in a positive and negative spraying mode. After the spinning was completed, a polylactic acid-glycolic acid nanofiber balloon was obtained. The positive high voltage was +5 kV, the spinning distance was 5 cm, the 23G needle was used, and the flow rate was 1 mL / h; the negative high voltage was -4.85 kV, the spinning distance was 5 cm, the 23G needle was used, and the flow rate was 1 mL / h; (3) 4.5 g of chitosan-silver composite particles were dispersed in a mixed solution of 75 mL of anhydrous ethanol and 25 mL of deionized water, ultrasonically treated for 20 min to obtain a chitosan-silver composite particle dispersion, then transferred to a syringe, and the syringe was fixed on the ultrasonic spraying machine. The chitosan-silver composite particle dispersion was uniformly sprayed onto the surface of the nanofiber balloon, dried, and a modified polylactic acid-glycolic acid nanofiber balloon was obtained. The ultrasonic current of the ultrasonic spraying machine was 3.6 A, the push flow rate was 1 mL / min, the reciprocating spraying frequency was 12 times, the spraying speed was 95 mm / min, the rotation speed was 60 mm / min, the nozzle height was 35 mm, and the carrier gas pressure was 0.038 MPa; (4) 5.5 g of polylactic acid-glycolic acid was dissolved in a mixed solvent of 40 mL of dichloromethane and 10 mL of N,N-dimethylformamide, and magnetically stirred at 30°C for 2 h to obtain a uniform solution. Then 0.2 g of modified polylactic acid-glycolic acid nanofiber balloon was added, and the mixture was continuously magnetically stirred at 30°C for 1 h to obtain a microneedle matrix material. Then the microneedle matrix material was added to the surface of the microneedle mold, centrifuged at a speed of 3500 r / min for 15 min, and then centrifuged at a speed of 3500 r / min for 8 min for drying to obtain a microneedle array; (5) 65 g of chitin fibers and 35 g of bamboo fibers were thoroughly mixed, carded and laid to obtain a fiber web, then treated by a hydroentanglement process, and a base cloth was obtained under a hydroentanglement pressure of 115 bar. Then 10 g of the base cloth was immersed in 200 mL of an ethanol aqueous solution containing 0.2% tea tree essential oil, and immersed at 40°C for 60 min. Finally, the ethanol and water were removed by hot air drying at 60°C for 30 min to obtain a mask base material. (6) The obtained microneedle array and mask base material were laminated under a sterile operating environment, then irradiated under a UV curing lamp for 30 s for curing to obtain an anti-infection microneedle mask.

[0028] Example 3: An anti-infection microneedle mask, the specific preparation steps are as follows: (1) Add 5g of chitosan to 100mL of deionized water, adjust the pH to 4 with glacial acetic acid, stir magnetically to dissolve, then add 2g of silver nitrate solution (10mmol / L) and stir to mix well, add 0.2g of sodium borohydride solution (100mmol / L) dropwise, stir vigorously for 15min, adjust the pH to 10 with ammonia, wait for precipitation to appear, centrifuge to separate, wash with deionized water 2-3 times and acetone 1-2 times, dry in a vacuum drying oven for 12h to obtain chitosan-silver composite particles; (2) Dissolve 1.5g of polylactic acid-glycolic acid in a mixed solution of 18g of dichloromethane and 9g of N,N-dimethylformamide, stir until homogeneous to obtain a polylactic acid-glycolic acid solution, then transfer it to a syringe and fix the syringe on an electrospinning machine. Spinning is performed using a positive and negative spraying method. After spinning is completed, polylactic acid-glycolic acid nanofiber capsules are obtained. The positive voltage is +5kV, the spinning distance is 5cm, the needle is 23G, and the flow rate is 1mL / h; the negative voltage is -4.85kV, the spinning distance is 5cm, the needle is 23G, and the flow rate is 1mL / h. (3) Take 5g of chitosan-silver composite particles and disperse them in a mixed solution of 80mL anhydrous ethanol and 20mL deionized water. Sonicate for 20min to obtain a chitosan-silver composite particle dispersion. Then transfer it into a syringe and fix the syringe on an ultrasonic spraying machine. Spray the chitosan-silver composite particle dispersion evenly onto the surface of the nanofiber capsule and dry it to obtain a modified polylactic acid-glycolic acid nanofiber capsule. The ultrasonic spraying machine has an ultrasonic current of 3.6A, a propulsion flow rate of 1mL / min, a reciprocating spraying number of 12 times, a spraying speed of 95mm / min, a rotation speed of 60mm / min, a nozzle height of 35mm, and a carrier gas pressure of 0.038MPa. (4) Dissolve 6g of polylactic acid-glycolic acid in a mixed solvent of 40mL dichloromethane and 10mL N,N-dimethylformamide, and stir magnetically at 30℃ for 2h to obtain a uniform solution. Then add 0.25g of modified polylactic acid-glycolic acid nanofiber capsules and continue to stir magnetically at 30℃ for 1h to obtain microneedle matrix material. Then add it to the surface of microneedle mold, centrifuge at 4000r / min for 20min, and then centrifuge at 4000r / min for 10min to dry to obtain microneedle array; (5) 70g of chitin fiber and 30g of bamboo fiber are thoroughly mixed, combed and laid to obtain a fiber web. Then, the fiber web is treated by hydroentanglement process with a hydroentanglement pressure of 120 bar to obtain a base fabric. Then, 10g of the base fabric is immersed in 200mL of ethanol aqueous solution containing 0.2% tea tree essential oil and treated at 40℃ for 60min. Finally, it is dried by hot air at 60℃ for 30min to remove ethanol and water and obtain the mask substrate. (6) The obtained microneedle array and the mask substrate are attached under a sterile operating environment, and then are placed under an ultraviolet light curing lamp for curing for 30 s to obtain an anti-infection microneedle mask.

[0029] Comparative Example 1: The difference from Example 2 is that no modified polylactic acid-glycolic acid nanofiber balloon is added, and the specific steps are as follows: (1) 5.5 g of polylactic acid-glycolic acid is dissolved in 40 mL of a mixed solvent of dichloromethane and 10 mL of N,N-dimethylformamide, and is magnetically stirred at 30°C for 2 h to obtain a uniform solution, thereby obtaining a microneedle substrate material, which is then added to the surface of a microneedle mold, centrifuged at a speed of 3500 r / min for 15 min, and then dried by centrifugation at a speed of 3500 r / min for 8 min to obtain a microneedle array; (2) 65 g of chitin fibers and 35 g of bamboo fibers are thoroughly mixed, carded, and laid to obtain a fiber web, which is then treated by a hydroentanglement consolidation process at a hydroentanglement pressure of 115 bar to obtain a base cloth, 10 g of the base cloth is then immersed in 200 mL of an ethanol aqueous solution containing 0.2% tea tree oil, and is immersed at 40°C for 60 min, and finally is hot air dried at 60°C for 30 min to remove ethanol and water to obtain a mask substrate; (3) The obtained microneedle array and the mask substrate are attached under a sterile operating environment, and then are placed under an ultraviolet light curing lamp for curing for 30 s to obtain an anti-infection microneedle mask.

[0030] Comparative Example 2: The difference from Example 2 is that the modified polylactic acid-glycolic acid nanofiber balloon is replaced by a polylactic acid-glycolic acid nanofiber balloon, and the specific steps are as follows: (1) 4.5 g of chitosan is added to 80 mL of deionized water, and the pH is adjusted to 3.4 by adding glacial acetic acid, and is magnetically stirred to dissolve, then 1.5 g of silver nitrate solution (10 mmol / L) is added and stirred to mix, 0.15 g of sodium borohydride solution (100 mmol / L) is added dropwise, and after stirring vigorously for 13 min, ammonia water is added to adjust the pH to 9.6, and after the precipitate appears, centrifugal separation is performed, and the precipitate is washed with deionized water for 2-3 times and acetone for 1-2 times, and is dried in a vacuum drying oven for 11 h to obtain chitosan-silver composite particles; (2) 1.4 g of polylactic acid-glycolic acid is dissolved in a mixed solution of 16 g of dichloromethane and 8 g of N,N-dimethylformamide to obtain a polylactic acid-glycolic acid solution, which is then transferred to a syringe, and the syringe is fixed on an electrospinning machine, and the electrospinning is performed by a positive and negative spraying mode, and after the electrospinning is completed, a polylactic acid-glycolic acid nanofiber balloon is obtained, wherein the positive high voltage is +5 kV, the spinning distance is 5 cm, the 23G needle is used, and the flow rate is 1 mL / h; the negative high voltage is -4.85 kV, the spinning distance is 5 cm, the 23G needle is used, and the flow rate is 1 mL / h; (3) 5.5 g of polylactic acid-glycolic acid was dissolved in 40 mL of a mixed solvent of dichloromethane and 10 mL of N,N-dimethylformamide, and was magnetically stirred at 30°C for 2 h to obtain a uniform solution, then 0.2 g of polylactic acid-glycolic acid nanofiber balloon was added, and was continuously magnetically stirred at 30°C for 1 h to obtain a microneedle matrix material, which was then added to the surface of a microneedle mold, centrifuged at a speed of 3500 r / min for 15 min, and then dried by centrifugation at a speed of 3500 r / min for 8 min to obtain a microneedle array; (4) 65 g of chitin fibers and 35 g of bamboo fibers were thoroughly mixed, carded, and laid to obtain a fiber web, which was then treated by a hydroentanglement consolidation process at a hydroentanglement pressure of 115 bar to obtain a base cloth, then 10 g of the base cloth was immersed in 200 mL of an ethanol aqueous solution containing 0.2% tea tree essential oil, and was immersed at 40°C for 60 min, and finally was hot air dried at 60°C for 30 min to remove ethanol and water to obtain a mask base material; (5) The obtained microneedle array and mask base material were laminated under a sterile operating environment, and then were irradiated under an ultraviolet light curing lamp for 30 s for curing to obtain an anti-infection microneedle mask.

[0031] Comparative Example 3: The difference from Example 2 is that the modified polylactic acid-glycolic acid nanofiber balloon is replaced by a mixture of polylactic acid-glycolic acid nanofiber balloon, chitosan, and silver nanoparticles, and the specific steps are as follows: (1) 5.5 g of polylactic acid-glycolic acid was dissolved in 40 mL of a mixed solvent of dichloromethane and 10 mL of N,N-dimethylformamide, and was magnetically stirred at 30°C for 2 h to obtain a uniform solution, then 0.15 g of chitosan, 0.14 g of polylactic acid-glycolic acid nanofiber balloon, and 0.01 g of silver nanoparticles were added, and were continuously magnetically stirred at 30°C for 1 h to obtain a microneedle matrix material, which was then added to the surface of a microneedle mold, centrifuged at a speed of 3500 r / min for 15 min, and then dried by centrifugation at a speed of 3500 r / min for 8 min to obtain a microneedle array; (2) 65 g of chitin fibers and 35 g of bamboo fibers were thoroughly mixed, carded, and laid to obtain a fiber web, which was then treated by a hydroentanglement consolidation process at a hydroentanglement pressure of 115 bar to obtain a base cloth, then 10 g of the base cloth was immersed in 200 mL of an ethanol aqueous solution containing 0.2% tea tree essential oil, and was immersed at 40°C for 60 min, and finally was hot air dried at 60°C for 30 min to remove ethanol and water to obtain a mask base material; (3) The obtained microneedle array and mask base material were laminated under a sterile operating environment, and then were irradiated under an ultraviolet light curing lamp for 30 s for curing to obtain an anti-infection microneedle mask.

[0032] Comparative Example 4: The difference from Example 2 is that the nanofiber balloon is replaced by nanofiber in step (2), and the specific steps are as follows: (1) 4.5 g of chitosan was added to 80 mL of deionized water, and glacial acetic acid was added to adjust the pH to 3.4. The solution was dissolved by magnetic stirring, then 1.5 g of silver nitrate solution (10 mmol / L) was added and stirred to mix, 0.15 g of sodium borohydride solution (100 mmol / L) was added dropwise, and the solution was stirred vigorously for 13 min. After the reaction, ammonia water was added to adjust the pH to 9.6. When the precipitate appeared, it was centrifuged and washed with deionized water 2-3 times and acetone 1-2 times. The precipitate was dried in a vacuum drying box for 11 h to obtain chitosan-silver composite particles; (2) 1.4 g of polylactic acid-glycolic acid was dissolved in a mixed solution of 16 g of dichloromethane and 8 g of N,N-dimethylformamide to obtain a polylactic acid-glycolic acid solution. The solution was then transferred to a syringe and fixed on an electrospinning machine. The nanofiber was obtained after spinning. The voltage was 12 kV, and the needle size was 23G (inner diameter 0.34 mm); (3) 4.5 g of chitosan-silver composite particles were dispersed in a mixed solution of 75 mL of anhydrous ethanol and 25 mL of deionized water, and ultrasonic treatment was performed for 20 min to obtain a chitosan-silver composite particle dispersion. The dispersion was then transferred to a syringe and fixed on an ultrasonic spraying machine. The chitosan-silver composite particle dispersion was uniformly sprayed onto the surface of the nanofiber, and the modified polylactic acid-glycolic acid nanofiber was obtained after drying. The ultrasonic current of the ultrasonic spraying machine was 3.6 A, the push flow was 1 mL / min, the reciprocating spraying frequency was 12 times, the spraying speed was 95 mm / min, the rotation speed was 60 mm / min, the nozzle height was 35 mm, and the carrier gas pressure was 0.038 MPa; (4) 5.5 g of polylactic acid-glycolic acid was dissolved in a mixed solvent of 40 mL of dichloromethane and 10 mL of N,N-dimethylformamide, and the solution was stirred magnetically at 30°C for 2 h to obtain a uniform solution. Then, 0.2 g of modified polylactic acid-glycolic acid nanofiber was added, and the mixture was stirred magnetically at 30°C for 1 h to obtain a microneedle matrix material. The matrix material was then added to the surface of a microneedle mold, and centrifuged at a speed of 3500 r / min for 15 min, and then dried by centrifugation at a speed of 3500 r / min for 8 min to obtain a microneedle array; (5) 65 g of chitin fibers and 35 g of bamboo fibers were thoroughly mixed, carded, and laid to form a fiber web. The fiber web was then treated by hydroentanglement process at a water jet pressure of 115 bar to obtain a base fabric. Then, 10 g of the base fabric was immersed in 200 mL of an ethanol aqueous solution containing 0.2% tea tree oil, and the immersion treatment was carried out at 40°C for 60 min. Finally, the ethanol and water were removed by hot air drying at 60°C for 30 min to obtain a mask base material; (6) Under a sterile operating environment, the obtained microneedle array and mask substrate are laminated, and then placed under an ultraviolet light curing lamp for irradiation for 30 s for curing to obtain an anti-infection microneedle mask.

[0033] Performance test: Microneedle puncture performance test: according to YY / T 1888-2023, microneedle array puncture force determination is carried out, a bionic skin model (PDMS, elastic modulus 1.5 MPa) is used, vertical puncture at a speed of 0.5 mm / s, and the peak puncture force is recorded; Antibacterial performance test: according to GB / T 20944.3-2008, experiments are carried out; Skin irritation test: according to GB / T 16886.10-2017, medical device biological evaluation is tested, New Zealand rabbits (n=6) are selected, the back hair is shaved, and the sample (4 cm x 4 cm) is pasted, and the erythema / edema reaction is observed after 24 h, and the classification is made according to the Draize scoring standard; Clinical trial observation: 70 healthy adults (18-45 years old) are selected and randomly divided into 7 groups (Examples 1-3, Comparative Examples 1-4), 10 people in each group, each person pastes the mask once a day, 30 min each time, and continuously uses for 7 days, after the test is completed, the data of the experimental personnel are collected, and the test results are shown in Table 1.

[0034] Table 1 Performance test results Microneedle penetration performance (N / needle) Antibacterial performance (%) Skin irritation Infection rate (%) Pain score (VAS) Example 1 0.92 99.9 0 level 0 0.8 Example 2 0.95 99.8 0 level 0 0.9 Example 3 0.90 99.7 0 level 1 1.0 Comparative Example 1 0.85 68.5 1 level 8 1.5 Comparative Example 2 0.88 75.2 0 level 5 1.2 Comparative Example 3 0.82 85.6 1 level 3 1.3 Comparative Example 4 0.20 72.3 2 level 10 2.5 From the data of Examples 1-3 in Table 1, it can be seen that the anti-infection microneedle mask prepared by the application exhibits excellent comprehensive performance, the microneedle puncture force is maintained in the stable interval of 0.90-0.95 N / needle, indicating that the three-dimensional nanofiber balloon structure constructed by the positive and negative electrospinning technology has ideal mechanical strength and penetration ability; the antibacterial performance reaches an extremely high level of 99.7-99.9%, which is speculated to be due to the uniform distribution of chitosan-silver composite particles on the surface of the nanofiber balloon forming a multiple antibacterial mechanism; the skin irritation is all 0 level, which may be due to the biocompatible wrapping layer of chitosan effectively blocking the direct contact of silver nanoparticles with the skin, and the sustained-release characteristics of the PLGA material avoiding the burst stimulation of active ingredients; the extremely low infection rate (0-1%) and pain score (0.8-1.0) suggest that the microneedle array can be precisely positioned to the epidermis, which not only ensures the transdermal delivery of the active ingredients, but also avoids the dermal nerve endings, and the breathable and moisturizing environment provided by the chitin-bamboo fiber base cloth further promotes the skin barrier repair.

[0035] From the data comparison of Example 2 and Comparative Examples 1-3 in Table 1, it can be inferred that the present application, by introducing the modified polylactic acid-glycolic acid nanofiber balloon structure, the excellent mechanical properties exhibited by Example 2 may be due to the unique stress distribution network of the three-dimensional nanofiber balloon, which forms an elastic support frame through the multidirectional connection of fiber nodes, both maintaining the rigidity of the microneedle and endowing it with moderate deformation ability, while the traditional simple mixed system (Comparative Example 3) or unmodified structure (Comparative Example 2) may result in a decrease in mechanical properties due to insufficient internal connection points; at the same time, the surface functionalization treatment of the modified balloon creates a more efficient active site distribution pattern, and the directional arrangement of chitosan molecular chains on the surface of nanofibers may form a continuous antibacterial barrier, while the increased density of silver nanoparticle anchoring sites promotes the sustained release of ions, and this ordered assembly structure can more effectively maintain the local antibacterial concentration compared to physical mixing (Comparative Example 3); in addition, the improvement in skin irritation reflects the encapsulation effect of the balloon structure on the active ingredients, and through the coating effect of chitosan and the degradation control of PLGA, a gradient release mechanism may be established, reducing the initial burst release of silver ions, while Comparative Example 1, which lacks this design, exhibits obvious irritation, and the difference in infection rate data further indicates that the three-dimensional porous structure of the modified balloon may optimize the spatial distribution of drug loading, forming a layered antibacterial defense line from the surface effect of rapid response to the deep protection of long-acting sustained release.

[0036] From the comparative data of Example 2 and Comparative Example 4 in Table 1, it can be seen that the present application achieves significant technical improvement through the design of the nanofiber balloon structure. This is mainly due to the three-dimensional fiber network constructed by the positive and negative counter-jet electrospinning process, which gives the material a more balanced mechanical property distribution, and this structure may enhance the overall deformation resistance through the stress dispersion effect of fiber nodes, while maintaining the sharpness of the microneedle tip; at the same time, the special morphology of the nanofiber balloon may provide a larger specific surface area and a more uniform distribution of active ingredients, allowing chitosan-silver composite particles to more fully contact microorganisms, while the planar fiber structure may result in uneven packing density, causing some antibacterial sites to be masked; and, the three-dimensional balloon structure is more effective in controlling the release of silver ions, which may reduce the burst release of active substances through the dual action of physical embedding and chemical bonding, optimizing the drug loading and release kinetics of the microneedle array and achieving more persistent maintenance of local antibacterial concentration.

[0037] It should be understood by those of ordinary skill in the art that the discussion of any of the above embodiments is merely exemplary and is not intended to suggest that the scope of the present application is limited to these examples; under the concept of the present application, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the present application as described above, which are not provided in detail for the sake of brevity.

Claims

1. A method for preparing an anti-infection microneedle facial mask, characterized in that, Includes the following steps: S1: Add chitosan to deionized water, adjust the pH to 3-4, then add silver nitrate solution and sodium borohydride solution, react for 10-15 min, adjust the pH to 9-10, centrifuge and wash the resulting precipitate, and dry it to obtain chitosan-silver composite particles. S2: Dissolve polylactic acid-glycolic acid in a mixed solution of dichloromethane and N,N-dimethylformamide, stir until homogeneous to obtain a polylactic acid-glycolic acid solution, then transfer it to a syringe and perform electrospinning using a positive and negative spraying method to obtain a polylactic acid-glycolic acid nanofiber capsule. S3: Chitosan-silver composite particles were dispersed in a mixed solution of anhydrous ethanol and deionized water to obtain a chitosan-silver composite particle dispersion. The dispersion was then transferred into a syringe, ultrasonically sprayed onto the surface of the nanofiber capsule, and dried to obtain a modified polylactic acid-glycolic acid nanofiber capsule. S4: Polylactic acid-glycolic acid is dissolved in a mixed solvent of dichloromethane and N,N-dimethylformamide to obtain a homogeneous solution. Then, modified polylactic acid-glycolic acid nanofiber capsules are added and magnetically stirred to obtain a microneedle matrix material. This material is then added to the surface of a microneedle mold, centrifuged, and dried to obtain a microneedle array. S5: Chitosan fiber and bamboo fiber are mixed and laid into a web, then hydroentangled to obtain a base fabric. The base fabric is then immersed in an ethanol aqueous solution containing 0.2% tea tree oil, treated at 40°C for 60 minutes, and dried to obtain a mask substrate. S6: Under aseptic conditions, the obtained microneedle array and the mask substrate are bonded together, and then cured under a UV curing lamp to obtain an anti-infection microneedle mask.

2. The preparation method according to claim 1, characterized in that, The ratio of chitosan, deionized water, silver nitrate solution, and sodium borohydride solution used in step S1 is 4-5g: 50-100mL: 1-2g: 0.1-0.2g.

3. The preparation method according to claim 1, characterized in that, The concentration of the silver nitrate solution in step S1 is 10 mmol / L; the concentration of the sodium borohydride solution is 100 mmol / L.

4. The preparation method according to claim 1, characterized in that, The weight ratio of polylactic acid-glycolic acid, dichloromethane, and N,N-dimethylformamide in step S2 is 1.2-1.5g:14-18g:6-9g.

5. The preparation method according to claim 1, characterized in that, In step S2, the electrospinning is performed with a positive high voltage of +5kV, a spinning distance of 5cm, a 23G needle, and a flow rate of 1mL / h; and a negative high voltage of -4.85kV, a spinning distance of 5cm, a 23G needle, and a flow rate of 1mL / h.

6. The preparation method according to claim 1, characterized in that, In step S3, the ratio of chitosan-silver composite particles, anhydrous ethanol, and deionized water is 4-5g:70-80mL:20-30mL.

7. The preparation method according to claim 1, characterized in that, The ultrasonic spraying machine described in step S3 has an ultrasonic current of 3.6A, a propulsion flow rate of 1mL / min, a reciprocating spraying frequency of 12 times, a spraying speed of 95mm / min, a rotation speed of 60mm / min, a nozzle height of 35mm, and a carrier gas pressure of 0.038MPa.

8. The preparation method according to claim 1, characterized in that, In step S4, the ratio of polylactic acid-glycolic acid, dichloromethane, N,N-dimethylformamide, and modified polylactic acid-glycolic acid nanofiber balloon is 5-6g:40mL:10mL:0.15-0.25g.

9. The preparation method according to claim 1, characterized in that, In step S5, the ratio of chitin fiber to bamboo fiber is 60-70g:30-40g; the ratio of the base fabric to an ethanol aqueous solution containing 0.2% tea tree oil is 10g:200mL.

10. An anti-infection microneedle facial mask, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Soluble microneedle patch, microneedle mask, microneedle smoking cessation patch and preparation method thereof

    CN119280105A